2018
DOI: 10.5551/jat.rv17024
|View full text |Cite
|
Sign up to set email alerts
|

Sitosterolemia, Hypercholesterolemia, and Coronary Artery Disease

Abstract: Sitosterolemia is a rare inherited disease characterized by increased levels of plant sterols, such as sitosterol. The cause of this disease is ATP-binding cassette (ABC) subfamily G member 5 or member 8 (ABCG5 or ABCG8, respectively) gene mutations. Recent advances in genetics have revealed that the prevalence of subjects with deleterious mutations in ABCG5 and/or ABCG8 genes could be more than 1 in ∼200,000 individuals among the general population. Furthermore, accumulated evidence, including infantile cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 29 publications
2
85
1
1
Order By: Relevance
“…Hematological investigations showed no stomatocytes, normal thrombocyte morphology and function, and no disturbance of hemostasis . Recently, it was suggested that “elevation of LDL‐cholesterol seems to be the major cause of development of atherosclerosis and not the elevation of sitosterols” rendering normalization of the cholesterol concentrations, as achieved in both patients, the primary treatment target.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hematological investigations showed no stomatocytes, normal thrombocyte morphology and function, and no disturbance of hemostasis . Recently, it was suggested that “elevation of LDL‐cholesterol seems to be the major cause of development of atherosclerosis and not the elevation of sitosterols” rendering normalization of the cholesterol concentrations, as achieved in both patients, the primary treatment target.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact prevalence of sitosterolemia is not known, it may be underdiagnosed and in fact more common than the estimated incidence of 1 in 1 000 000 . In fact, recent data indicate a prevalence of the disease more than 1 in ~200 000 individuals among the general population …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Familial sitosterolemia (OMIM #210250) is a rare Mendelian recessive disorder characterized by tendonous xanthomas 1 , high plasma plant sterols and cholesterol levels, and increased risk of premature myocardial infarction. [2][3][4] The ATP-binding cassette transporters G5 (ABCG5) and G8 (ABCG8) are primary causal genes of familial sitosterolemia. ABCG5,ABCG8, Niemann-Pick C1 Like 1 (NPC1L1) 5,6 determine the efflux and absorption of sterols on the surface of intestine and bile duct.…”
Section: Introductionmentioning
confidence: 99%
“…5,[10][11][12] Complete deficiency due to homozygous or compound heterozygous loss-of-function (LoF) variants in ABCG5 and/or ABCG8 causes markedly increased sitosterolemia and cholesterol levels, and potentially accelerated atherosclerotic disease as well. [1][2][3][4] Genome-wide association studies also demonstrated that loci at the ABCG5-ABCG8 gene region were associated with phytosterols, lowdensity lipoprotein (LDL) cholesterol, 13 and risk of coronary artery disease (CAD). 14 However, it is uncertain whether partial deficiency of ABCG5 or ABCG8 as conferred by LoF variants are also associated with higher cholesterol levels and an increased risk of CAD.…”
Section: Introductionmentioning
confidence: 99%